Population Dynamics of the Cuurisi Fish (Nemipterus hexodon) in the Waters of Flores Sea - Amir, Faisal; Nur, Ismy Adheliah; Umar, Moh. Tauhid (Agrikan Jurnal Agribisnis Perikanan, 2023)
The purpose of this research is to examine the population dynamics of cuurisi fish (Nemipterus hexodon) in the waters of Flores Sea, the parameters are cohort, growth parameters, and mortality parameters . This study took place between January and February of 2023. This study collected 1,214 samples. The data used is direct data in the field (primary data) by measuring the total length of cuurisi fish. Sampling was carried out using a stratified random sampling method. The Battacharya method using for analyze cohort, growth parameters (L? and K) were estimated using software electronic length frequency analysis (ELEFAN-I) contained in the FISAT-II application. Natural mortality (M) involves the empirical Pauly equation; total mortality (Z), fishing mortality (F), and exploitation rate (E) involve the Beverton and Holt equations. FISAT-II and Microsoft Excel were used to analyze the data. The results showed that the cuurisi fish samples had a total length range of 11–27 cm and consisted of three cohorts. The analysis results of L?, K, and t0 are 33.9 cm, 0.4 per year, and -0.398 years, respectively. The Z, M, and F estimates are 3.13; 096; and 2.17 per year, respectively. Exploitation rate 0.69; the actual and maximum Y/R’ were 0.0233 and 0.0241 g/recruitment, respectively. cuurisi fish in the waters of Flores Sea have slow growth, mortality is dominated by fishing activities, and have experienced overfishing.